The novel Mas agonist, CGEN-856S, attenuates isoproterenol-induced cardiac remodeling and myocardial infarction injury in rats. - Sílvia Q Savergnini (Public Library of Science (PLoS), 2013)
CGEN-856S is a novel Mas agonist. Herein, we examined the effects of this peptide on isoproterenol (ISO)-induced cardiac remodeling and myocardial infarction (MI) injury. We also sought to determine whether CGEN-856S activates the underlying mechanisms related to Mas receptor activation. Heart hypertrophy and fibrosis were induced by ISO (2 mg·kg(-1)·day(-1)) in Wistar rats. After a 7-day treatment period with CGEN-856S (90 µg·kg(-1)·day(-1)) or vehicle, the cardiomyocyte diameter was evaluated in left ventricular sections stained with hematoxylin and eosin, and immunofluorescence labeling and quantitative confocal microscopy were used to quantify the deposition of type I and III collagen and fibronectin in the left ventricles. MI was induced by coronary artery ligation, and CGEN-856S (90 µg·kg(-1)·day(-1)) or saline was administered for 14 days. The Langendorff technique was used to evaluate cardiac function, and left ventricular sections were stained with Masson's trichrome dye to quantify the infarct area. Using Chinese hamster ovary cells stably transfected with Mas cDNA, we evaluated whether CGEN-856S alters AKT and endothelial nitric oxide synthase (eNOS) phosphorylation. CGEN-856S reduced the degree of ISO-induced hypertrophy (13.91±0.17 µm vs. 12.41±0.16 µm in the ISO+CGEN-856S group). In addition, the Mas agonist attenuated the ISO-induced increase in collagen I, collagen III, and fibronectin deposition. CGEN-856S markedly attenuated the MI-induced decrease in systolic tension, as well as in +dT/dt and -dT/dt. Furthermore, CGEN-856S administration significantly decreased the infarct area (23.68±2.78% vs. 13.95±4.37% in the MI+CGEN-856S group). These effects likely involved the participation of AKT and NO, as CGEN-856S administration increased the levels of p-AKT and p-eNOS. Thus, our results indicate that CGEN-856S exerts cardioprotective effects on ISO-induced cardiac remodeling and MI-mediated heart failure in rats through a mechanism likely involving the eNOS/AKT pathway.